Sejarah dan Perbandingan Pendidikan Multikultural Di Negara Turki dan Belanda - Suprapno; Hifdzil Haq, Ahmad; Noer Aly, Hery; Zulkarnain, Zulkarnain; Ismail, Ismail (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2022)
The purpose of this study is to reveal and describe the history and development as well as a comparison of the application of the ideology of multiculturalism in every policy of the Turkish and Dutch governments. Especially about the history and comparison of multicultural education systems in Turkey and the Netherlands. The research method used is a historical-based qualitative method, considering that the data to be studied is an event that has occurred. This historical research approach is carried out by reviewing library data (library research). The analytical technique used in this research is descriptive qualitative analysis by discussing the data from primary sources readings with secondary sources reading data. The results show that these two countries both apply the ideology of multiculturalism and the application of multicultural education, this is done because these two countries are places for immigrants who have different backgrounds for escape, however, in the application of the multicultural education system of these two countries in its application, differences were found, this was caused by differences in the majority of religions in Turkey and the Netherlands. Differences in the application of a multicultural education system include the freedom of parents in choosing and extraordinary in determining state and private schools of their respective denominations in Turkey and the Netherlands, the important and very central role of the Turkish government is clearly visible in conceptualizing, implementing, and evaluating a curriculum that includes the value of multiculturalism and textbooks, compared to the multiculturalism policy in the Netherlands looks marginal and only makes adjustments and examinations of teaching materials that contain the ideology of multiculturalism